2012
DOI: 10.1080/15320383.2012.712072
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Trace Phthalic Acid Monoesters in Sediments and Soils by GC-MS

Abstract: A simple procedure for determining trace phthalic acid monoesters (PAMs) in sediments/soils was developed. The method used ultrasonic extraction, silylation derivatization, and GC-MS. After ultrasonic extraction, the supernatants were reextracted with dichloromethane, silylated, and did not require further clean-up before GC-MS analysis. Effects of parameters, such as extraction solvents, pH of water as extraction solvent and sediment/soil properties, on the recovery of PAMs were studied. Five sediments from T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…To determine the concentrations of MPEs, the dried plant tissue samples from both PAE- and MPE-treated groups, the soil samples, and cell material samples were spiked with deuterated MnBP and MEHP as recovery surrogates and then extracted in a sonication water bath with 15 mL of deionized water twice, 15 min for each extraction . The extracts were centrifuged at 3000 rpm for 30 min.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…To determine the concentrations of MPEs, the dried plant tissue samples from both PAE- and MPE-treated groups, the soil samples, and cell material samples were spiked with deuterated MnBP and MEHP as recovery surrogates and then extracted in a sonication water bath with 15 mL of deionized water twice, 15 min for each extraction . The extracts were centrifuged at 3000 rpm for 30 min.…”
Section: Methodsmentioning
confidence: 99%
“…19 The extracts were centrifuged at 3000 rpm for 30 min. The supernatants were combined and acidified to pH 2 with glacial acetic acid and then liquid−liquid extracted using 3 mL of methylene chloride (three consecutive times, each for 10 min).…”
Section: Environmental Science and Technologymentioning
confidence: 99%
See 2 more Smart Citations
“…For instance, Suzuki et al, observed MEHP in the Tama River in Tokyo at concentrations of 0.01–1.3 μg/L (2001). A recent study demonstrated that MEHP was detected in all sediment and soil samples ranged from 13.0 to 166.7 ng/g [14]. Moreover, MEHP has been widely detected in human biological samples such as milk, urine, saliva, and serum [15][19].…”
Section: Introductionmentioning
confidence: 99%